New insights into the chemical biodiversity of Minthostachys mollis in Argentina - van Baren, Catalina María (2014)
Variations in the chemical composition of the essential oils of Minthostachys mollis Griseb. (Lamiaceae) collected in their natural habitat in Argentina were determined using GC-FID-MS analysis. Seventy five samples collected out of 40 wild plant populations in the Central and Northwestern Argentina during four years sampling, were analyzed. Principal Component Analysis was made on the chemical data showing that samples from Córdoba and San Luis belonged to the typical menthone – pulegone chemotype in accordance with previous reports; meanwhile samples from Tucumán, Salta and Catamarca showed the presence of different compositions, some previously unreported, mainly those detected in Tucumán province. In addition, cluster analysis was applied using Euclidean distance to measure the dissimilarity in the relative composition of samples from Tucumán, Salta and Catamarca, using Ward's method as the agglomeration technique. Five groups were retained with less than 10% of information loss: i) dihydrocarvone-carvone, ii) pulegone with absence of menthone, iii) carvacryl acetate-carvacrol, iv) limonene and v) linalool. It is worth mentioning that the compositions of the different chemotypes remained constant throughout the four years of collection and despite the highly diverse pattern of compositions revealed in this search, the typical chemotype was not found present northwards Córdoba and San Luis provinces. This is the first report of a deep study on natural populations of peperina throughout the whole distribution area in Argentina with consecutive sampling repetitions of the same populations during several years.